2008
DOI: 10.1016/j.limno.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up or top-down – How is the autotrophic picoplankton mainly controlled? Results of long-term investigations from two drinking water reservoirs of different trophic state

Abstract: In two reservoirs of different trophic state, the abundance of autotrophic picoplankton was continuously assessed for 7 and 11 years, respectively. Simultaneously, other important environmental and biotic factors (nutrients, temperature, phyto-and zooplankton) were analysed. The mesotrophic Saidenbach Reservoir receives five-to sevenfold higher phosphorus imports, and exhibits twice higher phosphorus contents, and tenfold higher phytoplankton concentrations than the oligotrophic Neunzehnhain Reservoir. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…These findings confirm the results of Cherbi et al (2008). Thus zooplankton is an important grazer of algae and it is well known during periods of high zooplankton abundance (Horn et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…These findings confirm the results of Cherbi et al (2008). Thus zooplankton is an important grazer of algae and it is well known during periods of high zooplankton abundance (Horn et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, zooplankton is probably an important grazer of algae during periods of high zooplankton abundance. This is supported by the findings of a study by Horn and Horn (2008). There was no clear trophic gradient in Kasseb Reservoir; some horizontal differences in zooplankton abundance and community structure were observed.…”
Section: Discussionsupporting
confidence: 79%
“…It seems that in this treatment not only ciliates and NF, but also rotifers and crustaceans, which began to increase toward the end of the experiment, played an important role in controlling the picoplankton community. Although nanoflagellates are generally considered the main APP consumers (Callieri and Stockner 2002), Horn and Horn (2008) argue that crustaceans had the strongest effect on APP, basing their long-term study on observed inverse relationships between APP and various consumers groups. In our experiment, we demonstrated an active and successful replacement of various grazers of both picoplanktonic communities: eu-APP and bacteria.…”
Section: Direct Influence Of Large Grazersmentioning
confidence: 99%